Interference aware cluster-based joint channel assignment scheme in multi-channel multi-radio wireless mesh networks - Saqib Ali, 1977- , author; Md. Asri Ngadi, supervisor; Fakulti Kejuruteraan. Sekolah Komputeran (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2013)
Thesis (Doktor Falsafah, Bidang Penyelidikan: Sains Komputer)) - Universiti Teknologi Malaysia, 2013